Performance Analysis of Hydrocarbon Wells Based on the Skin Zone - Al-Obaidi, Sudad H; Khalaf, Falah H; Alwan, Hiba H (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The purpose of this research is to study the area near the bottom of the hydrocarbon well, which is usually affected by drilling and development operations, and to find a modern method that improves the transfer of fluid from the reservoir to the well. The area near the wellbore of an oil and gas formation is a very active and unstable zone. Field studies have shown that during the process of drilling the first well into the pay zone, a new area of disturbed permeability and porosity forms around the wellbore. This disturbed area is called the skin zone and is characterized by different properties. The skin zone can also form during the completion processes of hydrocarbon wells. In terms of well test processing for any hydrocarbon well, the term "skin effect" should be understood as the effect of changes in the lower wellbore zone (i.e., changes in rock properties, changes in formation fluid, formation structure, geologic section, etc.) on bottom wellbore pressure. This indicates a change in the permeability of the bottom zone of the borehole during drilling and development. In this paper, a new computational method is proposed in which the investigation of hydrocarbon well condition can be performed in two ways. The first way represents replacing the true radius of the wellbore (rw) with an effective radius (rwe). Under this condition, the skin factor term reflects only the effect of changes in the bottom wellbore zone. The second way is that the skin factor indicates not only the amount of change in the bottom wellbore zone, but also the effect of hydrodynamic imperfection of the hydrocarbon well performance during production, while maintaining the value of the well radius. After evaluating these parameters, it is possible to conclude the effectiveness of the implemented measures in the bottom wellbore zone of the formation. At the same time, the value of the skin factor after the performed works regarding the impact on the bottom zone can determine the positive or negative impact on the operation of the hydrocarbon well.